2018
DOI: 10.1021/acs.joc.8b02795
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Pyrido- and Pyrrolo[1,2-c][1,3]oxazin-1-ones via a Nucleophilic Addition–Cyclization Process of N,O-Acetal with Ynamides

Abstract: An efficient asymmetric approach to access functionalized pyrido-and pyrrolo[1,2-c][1,3]oxazin-1-ones has been developed through a nucleophilic addition−cyclization process of N,O-acetal with ynamides. A number of substituted ynamides 8a−8o and 3silyloxypyrrolidine or piperidine N,O-acetals 6a, 7 were amenable to this transformation, and the desired products 9a−9o, 10a−10m were obtained with excellent regioselectivities and outstanding diastereoselectivities. Moreover, chiral ynamides 14a−14f could also experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 82 publications
(26 reference statements)
1
22
0
Order By: Relevance
“…Then the scope and limitation of N ,O‐acetals 5 b and 5 c with different terminal alkynes 6 a – 6 l were also examined (Scheme ). First, the reaction of N ,O‐acetal 5 b with phenylacetylene 6 a successfully delivered the desired product 8 a in 75% yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then the scope and limitation of N ,O‐acetals 5 b and 5 c with different terminal alkynes 6 a – 6 l were also examined (Scheme ). First, the reaction of N ,O‐acetal 5 b with phenylacetylene 6 a successfully delivered the desired product 8 a in 75% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Our investigation started with the reaction of N ,O‐acetal 5 a with phenylacetylene 6 a . First, well‐known catalysts SnCl 4 and Bi(OTf) 3 were examined, and the results showed that catalytic amount of Bi(OTf) 3 could give the desired product 7 a in 9% yield, along with excellent diastereoselectivity ( dr >99:1) (Table , entries 1–3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Their intrinsic reactivity has been examined in relation with bioactive compounds of natural or synthetic origin, which incorporate such nucleophilic scaffolds. [16][17][18][19] Recently, Mayr group investigated the kinetics of the reactions of several pyrrolidine derivatives and they integrated the resulting constitutive parameters of pyrrolidines into the socalled Mayr's nucleophilicity scale. 16 On the other hand, thiophenes are heterocycles of industrial interest, 20,21 and substituted thiophenes are scaffold found within pharmaceuticals, conductive polymers, photochromic molecular switches, liquid crystals, etc.…”
Section: Introductionmentioning
confidence: 99%